Modelling and simulations for tourism and hospitality an introduction - Baggio, Jacopo A. 1980-; Baggio, Rodolfo (Bristol, UK Blue Ridge Summit, PA Channel View Publications, 2020)
This book offers an essential introduction to the use of various modelling tools and simulation techniques in the domains of tourism and hospitality. It aims to encourage students, researchers and practitioners in tourism and hospitality to enhance and enrich their toolbox in order to achieve a better and more profound knowledge of their field"--
Systems and tourism systems -- Models and modelling -- Methodological approaches -- Advanced modelling methods -- Choosing a modelling method -- A closing remake.
Includes bibliographical references and index.
Keywords: System analysis; Hospitality industry -- Mathematical models; Tourism -- Mathematical models; Hospitality industry -- Research -- Methodology; Tourism -- Research -- Methodology